PENGARUH DANA PİHAK KETİGA (DPK), INFLASİ DAN NON PERFORMİNG LOAN (NPL) TERHADAP PENYALURAN KREDIT PADA BANK UMUM Dİ PROVİNSİ RİAU TAHUN 2011(I)-2021(IV) - , Anthony Mayes, Nurhayati , Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to analyze the effect of variable Third Party fund (TPF), Inflation and Non Performing Loan (NPL) on credit distribution at public bank in riau province 2011(I)-2021(IV).  The type of data used in this study is quantitative and time series secondary data obtained from the publication of the Bank Indonesia (BI), Financial Services Authority (FSA) and Central Statistics Agency (CSA). Data analysis techniques used multiple linear regression analysis with the program Eviews 10. The hypothesis testing is carried out by statistical tests (t test, F test, coefficient of determination ), and classical assumption test.  The results of this study indicate that the Third Party Fund (TPF) variable has a positive and significant effect on the credit distribution. Inflation variable have a negative and significant effect on the credit distribution. Non Performing Loan (NPL) variable have a positive and significant effect on the credit distribution at public bank in Riau Province in 2011(I)-2021(IV).  Keyword : Credit Distribution, Third Party Fund (TPF), Inflation and Non Performing Loan (NPL)